Networks of prey specialization in an Arctic monomorphic seabird. (24th October 2013) - Provencher, Jennifer F.; Elliott, Kyle H.; Gaston, Anthony J.; Braune, Birgit M.
<x xml:space="preserve">Abstract</x> Generalist predator populations are sometimes made up of individuals that specialize on particular prey items. To examine specialization in thick‐billed murres Uria lomvia during self‐feeding we obtained stomach contents and muscle stable isotope values for 213 birds feeding close to five colonies in the Canadian Arctic. Adults were less specialized during self‐feeding than during chick‐provisioning. Nonetheless, particular specialists clustered together within the foraging network. While sexes showed similar levels of specialization, individuals of the same sex clustered together within the foraging network. The significant degree of clustering regardless of sex showed that individuals specializing on one prey item tend to also specialize on another, although network topology varied from colony to colony. Adult muscle stable isotope values correlated with the stable isotope values of the prey found in stomachs, at least at the one colony with relevant prey data, suggesting that specializations are maintained over time. Degree of specialization increased with niche width across the five colonies, but similarity in gastro‐intestinal and bill morphology was independent of dietary similarity. Thus, although individual specialization is thought to play a key role in sympatric speciation through trophic specialization, we found no support for an association between morphology and foraging patterns in our species. We conclude that self‐feeding murres show clustered dietary specialization, and that specialization is highest where diet is most diverse.